2009
DOI: 10.1161/strokeaha.108.543181
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Use of Intravenous rt-PA Thrombolysis Treatment for Acute Ischemic Stroke

Abstract: Background and Purpose-Some studies report that women are less likely to receive IV rt-PA treatment for stroke than men. We undertook a meta-analysis to determine whether a sex disparity existed. Methods-We identified studies that reported sex-specific IV rt-PA treatment rates for acute stroke. Eligible studies included acute stroke admissions from single or multiple hospitals, registries, or administrative databases. Random effects odds ratios (OR) and 95% confidence intervals (CI) were generated to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
89
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 45 publications
8
89
5
1
Order By: Relevance
“…A large meta-analysis found that women were consistently less likely to receive tPA than men across studies, while a nationally representative sample found no difference. 7,34 The evidence in the current study suggests no sex differences, and trends did not differ by sex. Similarly, previous research has shown that older stroke patients receive less care than younger patients, including fewer recommended diagnostic tests and treatments.…”
supporting
confidence: 41%
See 1 more Smart Citation
“…A large meta-analysis found that women were consistently less likely to receive tPA than men across studies, while a nationally representative sample found no difference. 7,34 The evidence in the current study suggests no sex differences, and trends did not differ by sex. Similarly, previous research has shown that older stroke patients receive less care than younger patients, including fewer recommended diagnostic tests and treatments.…”
supporting
confidence: 41%
“…1 Disparities exist in stroke care in the United States with differences in tissue plasminogen activator (tPA) use based on sex and race-ethnicity demonstrated in academic settings. [3][4][5][6][7] Temporal trends show that tPA use has more than doubled at large, high-volume academic hospitals since the early 2000s, with data suggesting that treatment gaps based on age and race are narrowing. [8][9][10] Yet there is a paucity of information concerning trends in community hospitals, which have been shown to exhibit different trends than academic centers.…”
mentioning
confidence: 99%
“…The lower use of intravenous thrombolysis in women is supported by a meta-analysis of 18 studies that showed a 30% lower odds for women to receive intravenous recombinant tissue-type plasminogen activator than men. 15 Although women were >7 years older and stroke symptom onset was more often unknown in women, our study depicted no sex differences in the use of intravenous recombinant tissue-type plasminogen activator with a thrombolysis rate of 14.5% for men and women. This is in accordance with a recent analysis by the Promoting Acute Thrombolysis for Ischaemic Stroke (PRACTISE) study investigators 16 and might be explained by a nowadays generally more wider application of intravenous thrombolysis beyond the previous classical contraindications such as especially higher age.…”
Section: Discussionmentioning
confidence: 54%
“…A number of studies have shown that women have more severe strokes than men [49]. It has also been estimated that women with acute ischemic stroke were 30% less likely to receive thrombolysis treatment with intravenous tissue plasminogen activator (tPA) than men [50]. Based on community studies, it has been found that women have a higher case of fatality rate than men, although confounders were not adjusted for all the studies.…”
Section: Effect Of Gender On Outcomesmentioning
confidence: 99%